Undervisningsbegreppets innebörd i förskolan utifrån ett läroplansteoretiskt perspektiv - Benita Berg (Educare)
The purpose of the study is to contribute knowledge about how teaching in preschool can be understood in relation to how teaching is described by preschool teachers. The following research questions were posed: How do preschool teachers describe teaching and its meaning in preschool? and What didactic questions appear in preschool teachers’ descriptions of teaching in preschool? The empirical data consist of reflective texts that were analysed through content analysis with the help of Bernstein’s concepts: classification and framing, and visible and invisible pedagogy. The results show that the preschool teachers in the study perceived the introduction of the concept of teaching in preschool as an opportunity, which allowed them to become more aware of their actions in different learning situations. That the preschool teachers described teaching taking place through play and in everyday situations based on children's interests and needs hints at an organization with invisible pedagogy, weak classification and weak framing. Strong classification and strong framing, on the other hand, became manifest when the preschool teachers described that they plan what they do with the children and use materials, organize children’s groups and design environments to promote children’s learning.  Furthermore, the preschool teachers focused mainly on the didactic questions of how and why, while the what-question received less attention.